2018
DOI: 10.3390/jcm7100368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Widespread Inotrope Use in Acute Heart Failure Patients

Abstract: Current guidelines recommend that inotropes should not be used in patients with normal systolic blood pressure (SBP). However, this is not supported with concrete evidence. We aimed to evaluate the effect of inotropes in acute heart failure (HF) patients from a nationwide HF registry. A total of 5625 patients from the Korean Acute Heart Failure (KorAHF) registry were analyzed. The primary outcomes were in-hospital adverse events and 1-month mortality. Among the total population, 1703 (31.1%) received inotropes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
2
7
0
1
Order By: Relevance
“…An interesting finding is that the use of intravenous diuretics was associated with lower in‐hospital mortality rate, as has been shown in recent studies 28 . By contrast, our analysis showed that intravenous inotrope and/or vasopressor use was an independent predictor of a detrimental outcome, which is consistent with the finding of previous studies 30–32 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An interesting finding is that the use of intravenous diuretics was associated with lower in‐hospital mortality rate, as has been shown in recent studies 28 . By contrast, our analysis showed that intravenous inotrope and/or vasopressor use was an independent predictor of a detrimental outcome, which is consistent with the finding of previous studies 30–32 …”
Section: Discussionsupporting
confidence: 92%
“…An outcome of this practice may have been iatrogenic hypotension and, as a consequence, the unjustified use of vasopressors and/or inotropes. Unfortunately, their use in patients with AHF has increased despite the evidence of their association with an increase in in‐hospital mortality 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…The results were similar with the previous reports by Kang et al showing that inotrope use was an independent predictor for in-hospital and 1-month postdischarge mortality in patients with initial sBP ≥90 mm Hg, but not in patients with an initial Open access sBP <90 mm Hg. 19 However, the categorisation of our patients into the sBP <90 mm Hg or cold group was mainly driven by 'cold' profile rather than sBP <90 mm Hg as more than 90% of this group had cold profile, whereas 85% had sBP ≥90 mm Hg. Given the limited options for medical management of decreased cardiac output and impaired peripheral organ perfusion, inotrope use might still be an option for patients with a cold profile.…”
Section: Discussionmentioning
confidence: 73%
“…Although much is known about the prognosis and outcomes of hemodynamically unstable patients started on IIT for cardiogenic shock, 5,9,10 little is known about the prognosis of hemodynamically stable patients with HF started on IIT, typically for inadequate responses to standard decongestion strategies. Given the increasing use of inotropes in the inpatient setting 10 and the increased diuretic resistance among contemporary hospitalized patients with HF, it is imperative that HF specialists and general cardiologists understand the implications and outcomes of starting IIT in hemodynamically stable patients.…”
mentioning
confidence: 99%
“…Such patients experience more arrhythmias, longer lengths of stay, increased in-hospital mortality, higher readmission rates, and increased costs. 3 , 4 , 5 , 6 , 7 , 8 However, none of these registries separate elective initiation as adjunctive therapy (ie, to augment diuresis) from the more common initiation as urgent therapy for progressive hemodynamic decompensation.…”
mentioning
confidence: 99%